ROOT CAUSES OF MIGRATION IN THE 21TH CENTURY (PANGEEA, 2025)
In recent years there has been a particularly large migration pressure on Europe. Geopolitical instability close to the continent triggered a huge wave of refugees, which unexpectedly reached the politically divided European Union. Although the phenomenon is not new, it is associated with a lot of conflict of interest. Different solutions from the EU and the Member States only tackled the situation in the short term, but the problem will continue in the coming years. Taking into account the global ecology and demographic processes, the proper management of migration is one of Europe's major challenges in the coming decades. Estimated immigration numbers can, however, increase considerably in the future. In addition to wars, ecological changes have a huge impact. Lack of water can be even more pressing in the years to come, as the phenomenon currently affects two billion people, and this number is likely to increase as forecasted. Global climate change is another source of difficulty, which accelerates environmental problems and indirectly contributes to migration processes.
Keywords: migration; climate change; demography